Brigadier General Charles King and his role in the Philippine Insurrection - Hanson, Jon H. (My University, 1974)
The purpose of this study is to determine the extent of the involvement of Brigadier General Charles King in the development of rifles used by the United States Army during the late nineteenth and early twentieth centuries, the last of the Indian wars, and the American participation in the Philippine Insurrection.
Keywords: Philippines -- History -- Philippine American War, 1899-1902; Krag-Jorgensen rifle; Philippines -- History -- 1898-1946; Springfield rifle; King, Charles, 1844-1933